Precision medicine in premature ovarian insufficiency: a focus on the precision therapeutic strategies for mesenchymal stem cells - Rou Wang; Fengyuan Liu; Qiuyue Liao; Jiachen Wu; Lingjuan Wang; Kezhen Li (Stem Cell Research & Therapy)
Abstract Premature ovarian insufficiency (POI) is one of the most common disorders that reduces fertility and the quality of life in young women. And mesenchymal stem cells (MSCs) have gradually been regarded as a promising therapeutic approach for POI for their potential in remodeling impaired ovarian function. However, specific details regarding the application of MSCs in POI treatment remain unclear. Key issues include the selection of appropriate MSCs sources, the optimization of culture conditions, and the determination of optimal transplantation protocols (encompassing dosage, administration route, and timing), all of which pose significant barriers to clinical translation of MSCs. Here, this paper systematically reviews the researches on MSCs-based POI therapy from mechanism to clinical application, with a focus on the key therapeutic details. Additionally, it highlights the application potential of fetal adnexa sources, in site transplantation, hypoxic environment and three-dimensional cultivation strategy for MSCs and provides an integrated analysis of MSCs’ dose efficacy inverted U-shaped relationship. Given the crucial role of MSCs’ targeting ability and therapeutic duration in precision medicine, this paper further explores the challenges, existing strategies, and future development directions of MSCs in this field, intending to provide a comprehensive reference for future research and clinical translation of MSCs in female ovarian diseases.